A fractional perspective on the trajectory control of redundant and hyper-redundant robot manipulators - Machado, J.A.Tenreiro (2016)
The manuscript develops a new perspective for studying the trajectory control of planar manipulators using the Moore–Penrose pseudoinverse. Different mechanical structures are compared, namely redundant and hyper-redundant robots. The proposed method is based on fractional calculus and fractional matrix powers. The signals can be interpreted as time- space waves propagating along the trajectory planing system. Several simulations demon- strate the performance of the novel scheme in the analysis of pseudoinverse-based closed- loop systems.